Концентрація та централізація капіталу в процесі економічного розвитку - Матвєєв, В'ячеслав Васильович; Нікітіна, Тетяна Андріївна (My University, 2012)
У статті досліджено та систематизовано основні причини, що спонукають капітал до концентрації та централізації, а також проаналізовано основні тенденції концентрації та централізації капіталу в процесі економічного розвитку.

In the article are made investigated and systemized the main reason which are prompting capital concentration and centralization, and also defined prerequisites, modern forms, tendencies and peculiarities of capital`s concentration in process of economics’ development. Also are summarizes the main reasons which contribute to the exit capital across national borders. The authors conclude that in the Global economy, the concentration of capital at the national level gradually develops into an international, supranational level. International monopolies, economic organizations and regional integration foundations are creating. National companies become to multinational corporations. Gradually the integration of transnational corporations and multinational banks takes place, which contributes to the appearance of transnational finance capital. Organizational forms of transnational corporations and transnational banks existing are national and international financial and industrial groups. Analysis of the dynamics concentration and centralization of the capital provides a basis to assert that the tendencies of further capital`s concentration and centralization of in various forms will be continue in the future.
Keywords: транснаціональний банк; капітал; концентрація капіталу; централізація капіталу; транснаціональна корпорація; ransnatsіonalny Bank; capital; kontsentratsіya kapіtalu; tsentralіzatsіya kapіtalu; transnatsіonalna korporatsіya; кафедра економічної теорії; кафедра економіки праці та менеджменту